The prognosis of cancer patients undergoing liposomal doxorubicin-based chemotherapy: A systematic review and meta-analysis. Issue 34 (27th August 2021) - Zhang, Kai-Ping; Fang, Xiang; Zhang, Yin; Chao, Min
Abstract: Background: It is well known that liposome-based delivery of cytotoxic chemotherapeutics has been proposed as a putative strategy to enhance drug tolerability and efficacy compared to the conventional chemotherapy. However, its potential effect on improving prognosis remains largely unknown. The current meta-analysis is to explore the prognosis of cancer patients undergoing liposomal doxorubicin-based chemotherapy. Methods: A detailed review of English and Chinese literature was conducted up to March 21, 2020. We evaluate its possible correlations using hazard ratios (HRs) with 95% confidence intervals (CIs). The pooled data were calculated by STATA software and Review Manager 5.3 software. Results: Consequently, 26 studies including 7943 patients were satisfied in current analysis. There were no significant differences between liposomal and conventional chemotherapy in OS (HR = 0.98, 95%CI: 0.93–1.04, P  = .544) and PFS (HR = 1.00, 95%CI: 0.92–1.10, P  = .945). Likewise, subgroup-analysis regarding country, cancer type, and sample sizes also showed the similar results of the 2 paired groups. Conclusion: Taken together, our finding has demonstrated that there was no association of undergoing liposomal doxorubicin-based chemotherapy with cancer prognosis. However, detailed and further studies are needed to confirm our conclusion.